Dynamics of antioxidant-prooxidant balance in abdominal injury with underlying hypovolemic shock and reperfusion syndrom of the limbs in experiment - V. O. Krylyuk; V. K. Grodetskyi; O. V. Fedoseyeva; S. V. Garian (Kazimierz Wielki University, 2020)
The article describes the results of the experimental study in which the effect of ischemic-reperfusion limb syndrome on changes in the internal organs was studied. Changes in the values of Malone dialdehalide, superoxide dismutase and catalase in the tissues of the kidneys, liver, lungs and muscles of the extremities were studied. These studies confirmed the hypothesis and proved the presence of signs of systemic changes as a result of applying a hemostatic tourniquet, the presence of potentiating effects of reperfusion syndrome with a combined injury of the abdominal cavity against the ground of hypovolemic shock.